Diversity and Abundance of Orchids at Gebugan Nature Reserve in Semarang, Indonesia - Tria Farokhah; Sri Utami; Jumari Jumari (Biosaintifika: Journal of Biology & Biology Education, 2018)
Orchid is a plant with a high aesthetic value.The existence of orchids directly by the community from their natural habitat, causing the existence of orchid in nature was threatened. The potential of orchid diversity in the Gebugan Nature Reserve area needs exploration to maintain its sustainability. This research would explore the diversity and abundance of orchid species and determined the environmental conditionof Gebugan Nature Reserve. The study was done on 2 stations with altitude difference are 900 m asl and 1045 m asl. Five plots of 10 m x 10 m were systematically constructed at each station with a distance of plots 50 meters. Species of orchids found in the Gebugan Nature Reserve were 12 species, including 11 species of epiphytic orchids and 1 species of terrestrial orchids. The abundance of individual orchid species was relatively higher in places with higher altitudes. Micropera sp was the most abundant orchid species and Corymborkis veratrifolia was the species of orchid with the lowest abundance. It is found that the environmental conditions of Gebugan Nature Reserve are suitable for orchid. The novelty of the research is providing a new data base of orchid in the Gebugan Nature Reserve. The result of the study would be beneficial for developing strategy of genetic conservation of orchird germplasm.